Pensamiento filosófico y desarrollo psicopedagógico en estudiantes de nivel secundaria de la Institución Educativa Primaria Secundaria N° 6010148 Balbina Dora Soto Correa, Caballococha 2025 - Amaringo Acosta, Rocio del Pilar (2026)
The aim of this research was to determine the relationship between philosophical thinking and psycho-pedagogical development in secondary school students at I.E.P.S. No. 6010148 Balbina Dora Soto Correa, Caballococha, during the year 2025. The study was based on a quantitative approach, with a non-experimental correlational cross-sectional design, using questionnaires as data collection instruments. The results indicated that, in the philosophical thinking variable, 55.7% of students were at a low level, 28.6% at a high level, and 15.7% at a medium level. In relation to the variable of psycho-pedagogical development, 57.1% presented a medium level, 30.0% a high level, and 12.9% a low level. Spearman's correlation coefficient was 0.879, which shows a high positive correlation between the variables. Furthermore, the significance value obtained (p = 0.000) confirms that the relationship between philosophical thinking and psycho-pedagogical development in students is statistically significant.